PDU-Scale Experimental Results of CO2 Removal With Amp/Pz Solvent - Śpiewak Dariusz; Krótki Aleksander; Spietz Tomasz; Stec Marcin; Więcław–Solny Lucyna; Tatarczuk Adam; Wilk Andrzej (Chemical and Process Engineering)
:This paper provides a discussion concerning results of CO2 removal from a gas mixture by the application of aqueous solutions of ethanoloamine (MEA) and 2-amino-2-methyl-1-propanol (AMP) promoted with piperazine (PZ). The studies were conducted using a process development unit. Research of such a scale provides far more reliable representation of the actual industrial process than modelling and laboratory tests. The studies comprised comparative analyses entailing identical energy supplied to a reboiler as well as tests conducted at similar process efficiencies for both solvents. The results thus obtained imply that using AMP/PZ enables reduction of the solvent heat duty. Moreover, while using AMP/PZ temperature decrease was also observed in the columns.